RANCANGAN GEOMETRI PELEDAKAN YANG EFISIEN UNTUK MENDAPATKAN DISTRIBUSI UKURAN FRAGMENTASI BATU GAMPING - Murad; Septami Setiawati; Wahdaniah Mukhtar (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2023)
The rock fragmentation distribution resulting from blasting is one of the important factors of the blasting method design model for dismantling excavated materials. Calculation of rock fragmentation resulting from blasting using the RL theory. Ash, CJ. Konya, and ICI-Explosive. The method for determining the size of rock fragmentation resulting from blasting and analysis of the fragmentation size distribution in blasting activities uses the Kuz-Ram method and Split Desktop 4.0 software. A good blasting geometry design from a technical and economical point of view enables achieving target production according to the design made by the company in producing an average fragmentation size of limestone <50 cm. Blasting geometry applied by PT. Semen Padang produces a hole volume of 275 m3 with a fragmentation of 53.46 cm. The results of the fragmentation design are based on the RL Ash theory and the Kuz-Ram method with a volume of300.67 m3each hole anda fragmentation size of 50.07 cm, CJ. Konya analysis resulted in a hole volume of 422.4 m3 with an average fragmentation of 44.17 cm, and ICI-Explosive method resulted in a hole volume of 285 m3 with an average fragmentation of 47.86 cm. Based on blasting geometry calculation, fragmentation analysis and economic calculations, it is shown that the blasting geometry suggestion using CJ Konya theory is more optimal and feasible to apply because it results in a larger hole blasting volume, higher percentage of fragmentation of <50 cm which is compatible with the bucket capacity, as well as higher revenue and profit compared to the other two methods.